The extent of commitment of Iraqi banks to the International Financial Reporting Standard (IFRS) 7: Financial Instruments: Disclosures - Jachi, Moses; Kareem, Hussein; Kendory, Emad (International Journal of Psychosocial Rehabilitation, 2020)
With the obligation for Iraqi entities to fully comply with International Financial Reporting Standards (IFRS) evidently declared in Iraqi companies in order to provide more transparent information to the users of financial statements. The purpose of this study is to assess the extent of Iraqi banks’ commitment to fully applying the International Financial Reporting Standard 7 disclosure requirements. The researcher uses the method of factor analysis and variance analysis to achieve that goal. In compliance with the disclosure standards of IFRS 7, the analysis found that the relative value of transparency in the financial statements (income statement, financial position statement, and cash flow statement) is not comparable. With obvious confirmation of the lack of statistical significance between the existence and size of the relevant statements as per the income statement, the financial position statement, and the banks’ cashflow statement in Iraq. The study findings confirm conclusions from prior studies that claim poor disclosure quality in light of IFRS 7 as a continuing phenomenon, pointing to this as a result of deliberate lack of commitment by banks to fully comply with disclosure requirements stipulated by IFRS 7.